Diagnostic and prognostic value of sex- and age-specific cutpoints for high-sensitivity Troponin T in non-ST-elevation acute coronary syndrome. (15th January 2019) - Widera, Christian; Giannitsis, Evangelos; Mueller-Hennessen, Matthias; Reimann, Ines; Guba-Quint, Anja; Marquardt, Ivonne; Bethmann, Kerstin; Meyer, Sven
Abstract: Introduction: Sex- and age-specific high-sensitivity Troponin T (hs-cTnT) cutpoints for the diagnosis and prognosis in acute coronary syndromes are not well established. We evaluated the use of such dichotomous thresholds for calculation of the GRACE score. Methods: We analyzed a retrospective cohort study of 1146 patients with non-ST-elevation acute coronary syndrome (NSTE-ACS). Sex-dependent hs-cTnT cutpoints comprised 15.5 ng/L for men and 9.0 ng/L for women, while the sex-/age-specific cutpoints comprised 17 ng/L for 50–64-year-old men and ≥65-year-old women, 31 ng/L for ≥65-year-old men and 14 ng/L for the remainder of patients. Results: For the diagnosis of NSTEMI using sex-specific hs-cTnT cutpoints, in women, the positive likelihood ratio (LR+) was 2.04 (1.68–2.47) while in men, the negative likelihood ratio (LR−) was 0.05 (0.04–0.07). Using sex-/age-specific hs-cTnT cutpoints, in ≥65-year-old women the LR− was 0.09 (0.06–0.15), in 50 to 64-year-old men the LR− was 0.08 (0.04–0.13) while in ≥65-year-old men the LR− was 0.32 (0.28–0.37). Sex-specific hs-cTnT cutpoints achieved an NRI of −0.020 (95% CI, −0.101–0.118) for women and 0.030 (95% CI, −0.013–0.079) for men, and the sex-/age-specific hs-cTnT cutpoints achieved an NRI of 0.061 (95% CI, −0.019–0.132) for women and 0.021 (95% CI, −0.062–0.108) for men, while net benefit and clinical utility were highest for women using the sex-/age-specific hs-cTnT cutpoints. Conclusions: Sex-dependent hs-cTNT cutpoints imply increasing diagnostic sensitivity for women at the cost of specificity. Considering age for hs-cTNT cutoffs slightly improves risk reclassification, although the overall gain in terms of the clinical management appears negligible. Highlights: Sex-dependent hs-cTNT cutpoints increase diagnostic sensitivity for women and reduce specificity. Considering sex-/age-dependent hs-cTnT cutoffs slightly improves risk reclassification. The overall gain of sex-/age-dependent hs-cTnT cutoffs appears negligible.